MEN AND SOCIAL TRAUMA OF COVID-19 PANDEMIC. THE MALADAPTIVENESS OF TOXIC MASCULINITY - FRĄCKOWIAK-SOCHAŃSKA, MONIKA (Society Register, 2021)
The first purpose of this paper is to analyze the direct and indirect, short- and long-term consequences of the COVID-19 pandemic for men. The second purpose is to identify the mechanisms underlying the present and predicted pandemic’s impact on men’s life and health (both somatic and mental). The author interprets the higher men's mortality due to coronavirus rates and the males' suicide rates that heightened from the beginning of the pandemic due to life-style that reflects the toxic masculinity norms. This paper's theoretical framework is determined by the social (cultural) trauma theory and the Critical Studies on Men and Masculinities. The method used for the present study is desk research based on the integrated literature review including the results of empirical research directly or indirectly addressing males’ experience of the COVID-19 pandemic from the years 2019 and 2020, the previous pandemics (SARS in 2002-2004 and Ebola in 2014), other social crises caused by economic and political processes, and research explaining men’s stress-related behaviors.